COMPARISON OF ABBREVIATED BURN SEVERITY INDEX (ABSI) SCORE WITH R-BAUX SCORE AS A PREDICTOR OF MORTALITY IN BURN PATIENTS - Melissa Anita Ayu Iustitiati; Beta Subakti Nata’atmadja (Jurnal Rekonstruksi dan Estetik)
HIGHLIGHTS: